Analisis Faktor-Faktor yang Mempengaruhi Laju Pertumbuhan Ekonomi di Kabupaten Sumbawa Tahun 2011-2020 - Hanifa Sri Nuryani; Edi Irawan (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to identify and analyze the factors that influence the rate of economic growth in Sumbawa Regency in 2011 - 2020. The research method used in this study is a quantitative method, using secondary data from the Sumbawa Regency BPS. Analysis of the data used is the multiple regression method with the Ordinary Least Square (OLS) technique. The results of the study show that investment in the MSME sector, the number of working people and the HDI in Sumbawa Regency together have a significant effect on economic growth in Sumbawa Regency. This can be seen in the F test where the significance value is less than 0.05 (0.002 < 0.05). Then the magnitude of the influence on each of the independent variables mentioned above varies. The highest influence is found in the investment variable in the MSME sector of 6.022%. then the HDI is 0.408%. And the number of working population is 0.000%. So the investment variable in the MSME sector in Sumbawa Regency has the greatest impact on the rate of economic growth in Sumbawa Regency.